A study on otorhinolaryngology related emergency surgical procedures performed under general anaesthesia in a teaching hospital - Koirala, Krishna P.; Karki, Bikram B.; Maharjan, Manita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Most of the ear, nose and throat related disorders that present in emergency can be managed without anaesthesia. Some of them are potentially life threatening and critical requiring surgical interventions under general anaesthesia, too. Ear, nose, and throat related emergency conditions are in rise due to increased incidence of road traffic accidents, social violence and physical assault. This study was performed to find out common ear, nose, throat and head and neck related emergency conditions that required emergency surgical procedures under general anaesthesia for their treatment. Methods: One hundred and seventy-seven patients were enrolled in this prospective cross-sectional study. Patients who underwent emergency operative procedures under general anaesthesia were assessed to find out the common reasons of admission and the common procedures performed for their treatment. Results: Out of 177 patients enrolled in the study, 26.6% were children below the age of 10 years. About three fourths (74.6%) had presented with foreign body in the ear, nose, or throat, and about 77% of them requiring anaesthesia were foreign bodies of the esophagus. Next most common surgical procedures were performed for different traumatic injuries (23.7%). Rest 1.7% of patients required other procedures like tracheostomy, sphenopalatine artery cauterization and traumatic split lobule repair under general anaesthesia. Conclusions: Foreign bodies in the ear, nose and throat are the most common emergency conditions requiring emergency surgery under general anaesthesia followed by traumatic cut injuries in our institution. Prompt treatment of the emergency condition is required for the better patient outcome.